Variasi Spasial Sosial Ekonomi Masyarakat di Wilayah Pertambangan Emas Bone Bolango - Aan Apriyanto Maini; Sri Maryati; Moch. Rio Pambudi (Universitas Negeri Gorontalo, 2026)
Gold mining affects community socio-economic conditions differently due to variations in accessibility, human resources, and economic opportunities. This study aimed to describe community socio-economic conditions, analyze their spatial variations, and identify the factors influencing these variations in Suwawa Timur and Pinogu Districts, Bone Bolango Regency. A quantitative descriptive-spatial survey was conducted involving 94 households selected from both districts. Data were collected through questionnaires, observations, documentation, and secondary sources, then analyzed using descriptive statistics and spatial interpretation. The results showed that the community's socioeconomic conditions were characterized by the dominance of agriculture and mining as the primary livelihoods, with household incomes ranging from IDR 500,000 to IDR 1,000,000 per month. Spatial differences indicate that Suwawa Timur has more diverse socio-economic characteristics than Pinogu. These variations are associated with differences in educational attainment, regional accessibility, and livelihood structure.